Design and implementation of an integrated pipeline security system with optmized scheduling - Akpovi Oyubu Oyubu; Ufuoma Kazeem Okpeki (Institute of Advanced Engineering and Science, 2021)
Offshore equipment and facilities are some of the most capital intensive and strategically located assets that require millions to billions of dollars to setup. Thus, it is important to put in place a stout security and surveillance system to ultimately protect these assets from vandalisation and theft. Monitoring of intruders/ unfamiliar objects within and outside the offshore platform requires a round-the-clock observation through provided security personnel who are stationed so as to quickly respond to any threat within a safe distance in the event of any physical intrusion but this measure is fraught with some challenges. Some of these challenges include fatigue, error in human judgement, and the limited vision of humans to mention but a few. To remedy these weaknesses and ensure a robust protection, the design and implementation/ setting up of a surveillance system to detect and track real time security concerns with a much wider and effective coverage area to enable the control unit make a well informed decision appropriately is an imperative. The system presented in this paper is designed to operate in harsh (sea waves, and fog) and unprotected (extreme heat, cold precipitation) environment.